Capacity Accumulation and Utilization in a Differential Duopoly Game - Roberto Cellini; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
We present a different duopoly game with capacity accumulation, where firms control investment effords and sales, which can be at most equal to the respective installed capacities at any point of time. We use, alternatively, inverse and direct demand functions with product differentiation, recalling Cournot and Bertrand competition. We show that, at the subgame perfect steady state equilibria, Cournot and Bertrand profits do not coincide, unless the game is quasi-static, which happens if capacity does not depreciate over time.
Keywords: 330